Governing ethnic unrest: Political Islam and the Kurdish conflict in Turkey. (November 2019) - Günay, Onur; Yörük, Erdem
Abstract: How can we explain the mass appeal and electoral success of Islamist political parties? What are the underlying sources of the Islamist political advantage? Scholars have provided numerous answers to these widely debated questions, variously emphasizing the religious nature of the discourses in Islamist movements, their ideological hegemony, organizational capacity, provision of social services, reputation, and structural factors. However, one key aspect of Islamist movements has been underexplored in the current literature; namely, Islamists' promises to resolve ethnic questions that remain unresolved in secularist nation-states. In this article, we argue that the extent to which Islamists govern ethnic unrest significantly shapes their electoral success and ability to establish broader hegemony. Based on ethnographic and sociological data, this article explores one particular recent electoral puzzle that reveals the limits of the scholarly literature on Islamist political advantage, examining the ethnic politics of the governing Justice and Development Party ( Adalet ve Kalkınma Partisi, AKP) in Turkey.